Note on the efficiency of adiabatic shock - Morley, A. W. (College of Aeronautics, Cranfield, 1948)
This note records some calculations of the efficiency of adiabatic shock in air (x=1.4); where the efficiency is defined as the ratio of the work used to compress the air in the shock wave, from the inlet static to the outlet total head pressure, to the work required if the compression were isentropic.